2015
DOI: 10.1590/s1516-8913201400276
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Scopolamine content in Hairy Roots of Atropa belladonna using Bioreactor

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 38 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Additionally, by manipulating metabolic pathways (introducing new genes or silencing selected ones), it is possible to create efficient plant-based production systems. Plant cells or tissue cultures obtained in this way can be transferred to bioreactors, allowing them to be cultivated on a larger scale, which can directly lead to a further increase in productivity and even their use on an industrial scale [ 33 , 34 ]. The entire set of factors described above makes it possible to develop highly efficient plant culture systems, the metabolites of which can be used in the pharmaceutical and medical industries [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, by manipulating metabolic pathways (introducing new genes or silencing selected ones), it is possible to create efficient plant-based production systems. Plant cells or tissue cultures obtained in this way can be transferred to bioreactors, allowing them to be cultivated on a larger scale, which can directly lead to a further increase in productivity and even their use on an industrial scale [ 33 , 34 ]. The entire set of factors described above makes it possible to develop highly efficient plant culture systems, the metabolites of which can be used in the pharmaceutical and medical industries [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Habibi et al [ 56 ] reported that apart from aeration, media, and culture agitation can also be important factors, which enhanced cell growth and increased scopolamine production of Atropa belladonna hairy roots in bioreactor. BCB cultivation involves mechanical stress caused by inflows of air and high agitation, which often results in some slight damage of hairy roots that manifests as foaming of growth medium.…”
Section: Discussionmentioning
confidence: 99%
“…belladonna Hairy root cultures were produced by inoculating sterile leaf explants with Agrobacterium rhizogenes strain 15834 (Habibi et al 2015) (Fig. 1a).…”
Section: Methodsmentioning
confidence: 99%